Algoritma SMART dalam Sistem Penilaian Karyawan Terbaik Berbasis Web - Sukaesih, Fitri; Mugiarso; Mukhlis; Rasim (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2025)
PT Sinar Perkasa Engineering is a leading engineering and manufacturing company that considers employee evaluation a critical component of human resource management. Manual evaluation processes are often time-consuming and prone to human error, potentially leading to inaccuracies in selecting the best employees. This study aims to design a decision support system based on the SMART algorithm to enhance the efficiency and accuracy of employee evaluations. The system was developed using the Waterfall model and designed with the Unified Modeling Language (UML). The results indicate that the implementation of a web-based decision support system significantly improves the speed and accuracy of the evaluation process, reduces the risk of human error, and provides a transparent and objective assessment tool. This research is expected to serve as a foundation for further development of decision support systems, either through collaborative efforts or by comparing alternative decision-making methods.